The Role of Pioneering Aviation in Building Remote Area Connectivity: Development Law Theory, Progressive Law Theory and Integrative Law Theory - Tazkira, Ifa Titha (Balobe Law Journal, 2025)
Introduction: The geographical condition of Indonesia, where most of its territory consists of islands and archipelagos with many areas still isolated and difficult to reach, makes pioneer air transportation a potential solution for sustainable infrastructure development.Purposes of the Research: In order to understand the relevant legal perspectives regarding the role of pioneer air transportation in remote areas, this can be viewed from the combination of development law theory and progressive law theory, reinforced by integrative law theory.Methods of the Research: Using a normative juridical method, this research examines the law based on legislation related to the issues being studied. The research approach involves a conceptual approach, a statutory approach, and a case approach.Results of the Research: This writing examines the integration of three theories: development law theory, progressive law theory, reinforced by integrative law theory, in the role of pioneer air transportation to build connectivity in remote areas amidst various challenges. One of the main challenges is the difficult geographical conditions and limited infrastructure. Many isolated areas can only be accessed by air transportation; however, airport facilities and runways are often inadequate to support safe and efficient flight operations. The principle of sovereignty over airspace is the starting point for regulating most issues in international air law. With the presence of pioneer aircraft, areas that were previously isolated from economic or governmental centers become more accessible, which in turn opens up opportunities for the distribution of goods, services, and other resources.